Stereochemically Reliable Syntheses of Pachastrissamine and Its 2-epi-Congener via Oxazolidinone Precursors from an Established Starting Material N-tert-Butoxycarbonyl-Protected Phytosphingosine - Bae, Hoon; Jeon, Hongjun; Baek, Dong Jae; Lee, Dongjoo; Kim, Sanghee (Synthesis, 2012)
Efficient, stereochemically unambiguous, total syntheses of pachastrissamine and its 2-epi-congener from the readily available common precursor (1R)-1-{(4S,5S)-2-oxo-4-[(trityloxy)methyl]-1,3-oxazolidin-5-yl}pentadecyl methanesulfonate are reported. Syntheses of (3aS,6R,6aR)- and (3aS,6S,6aR)-6-tetradecylhexahydro-2H-cyclopenta[d][1,3]oxazol-2-one by this route have unambiguously resolved a dispute over the structures of these products.
Keywords: natural products; stereoselective synthesis; heterocycles